Psychosocial screening and assessment in oncology and palliative care settings - Grassi, Luigi; Caruso, Rosangela; Sabato, Silvana; Massarenti, Sara; Nanni, Maria G.; the UniFe Psychiatry Working Group Coauthors, (Frontiers in Psychology, 2015)
Psychiatric and psychosocial disorders among cancer patients have been reported as a major consequence of the disease and treatment. The problems in applying a pure psychiatric approach have determined the need for structuring more defined methods, including screening for distress and emotional symptoms and a more specific psychosocial assessment, to warrant proper care to cancer patients with psychosocial problems. This review examines some of the most significant issues related to these two steps, screening and assessment of psychosocial morbidity in cancer and palliative care. With regard to this , the many different variables, such as the factors affecting individual vulnerability (e.g. life events, chronic stress and allostatic load, well-being, and health attitudes) and the psychosocial correlates of medical disease (e.g. psychiatric disturbances, psychological symptoms, illness behavior, and quality of life) which are possibly implicated not only in “classical” psychiatric disorders but more broadly in psychosocial suffering. Multidimensional tools (e.g. and specific psychosocially oriented interview (e.g. the Diagnostic Criteria for Psychosomatic Research - DCPR) represent a way to screen for and assess emotional distress, anxiety and depression, maladaptive coping, dysfunctional attachment, as well as other significant psychosocial dimensions secondary to cancer, such as demoralization and health anxiety. Cross-cultural issues, such as language, ethnicity, race, and religion, are also discussed as possible factors influencing the patients and families perception of illness, coping mechanisms, psychological response to a cancer diagnosis.